2017
DOI: 10.14434/pders.v36i2.23718
|View full text |Cite
|
Sign up to set email alerts
|

Use of Video Modeling to Teach Weight Lifting Techniques to Adults with Down Syndrome: A Pilot Study

Abstract: Abstract:As adults with Down syndrome (DS) age, their strength decreases resulting in difficulty performing activities of daily living. In the current study, we investigated the use of video modeling for teaching three adults with DS to perform weight lifting techniques. A multiple probe design across behaviors (i.e., lifts) was used to evaluate intervention effectiveness. Data indicated variable effects across participants and lifting techniques. Limitations and suggestions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Video modelling, which has been used in various disciplines for effective at-home learning (Bellini & Akullian 2007;Biederman & Freedman 2007), was added to DSFit 2 after the majority of parents in DSFit 1 indicated in their feedback survey that they thought this feature could be helpful for home practice. Video modelling has been shown to be a useful technique to teach new skills to children and adults with DS, and there is emerging research suggesting it may be useful for specifically teaching exercise skills as well (Carter et al 2017). However, findings from our follow-up survey showed that most families were not using the videos 2 months after the programme ended.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Video modelling, which has been used in various disciplines for effective at-home learning (Bellini & Akullian 2007;Biederman & Freedman 2007), was added to DSFit 2 after the majority of parents in DSFit 1 indicated in their feedback survey that they thought this feature could be helpful for home practice. Video modelling has been shown to be a useful technique to teach new skills to children and adults with DS, and there is emerging research suggesting it may be useful for specifically teaching exercise skills as well (Carter et al 2017). However, findings from our follow-up survey showed that most families were not using the videos 2 months after the programme ended.…”
Section: Discussionmentioning
confidence: 66%
“…Video modelling has been shown to be a useful technique to teach new skills to children and adults with DS, and there is emerging research suggesting it may be useful for specifically teaching exercise skills as well (Carter et al . 2017). However, findings from our follow‐up survey showed that most families were not using the videos 2 months after the programme ended.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a larger body of literature on interventions focused on physical health behaviors such as exercise for this population (e.g., [6][7][8][9]), interventions to support healthier nutrition habits is lacking. When compared to individuals without IDD, fewer people with IDD meet recommended guidelines for each food group, except for sugar and fat [10].…”
Section: Introductionmentioning
confidence: 99%